Un nuevo impulso interamericano a favor de la justiciabilidad del derecho ambiental - González Palacios, Carlos; Taipe Chirito, Mariafernanda; Padilla Arce, Ela; Parodi Ccoriñaupa, Camila (Universidad ESAN, 2025)
Although the direct justiciability of environmental law is not provided for in the Pact of San José, the consistent jurisprudence of the Inter-American Court in cases involving indigenous peoples has led to the development of a broad interpretation of Article 26 of the Pact. This interpretation, in the ruling in Inhabitants of La Oroya v. Peru, assumes a scope that guarantees third-generation rights. In this case, the Inter-American judge ruled for the first time in detail on the obligations of States regarding their duty to prevent, regulate, and punish environmental damage.

Si bien la justiciabilidad directa del derecho ambiental no está prevista en el Pacto de San José, la jurisprudencia constante de la Corte Interamericana en casos relacionados con pueblos indígenas ha dado lugar al desarrollo de una interpretación amplia del artículo 26 del Pacto. Esta interpretación, en la sentencia Habitantes de La Oroya vs. Perú, asume un alcance garantista de los derechos de tercera generación. En este caso, el juez interamericano se pronunció por primera vez con detalle sobre las obligaciones de los Estados en torno a su deber de prevenir, regular y sancionar el daño ambiental.
Keywords: Environmental Law; Inter-American Law; Human Rights; Pact of San José; Derecho ambiental; Derecho interamericano; Derechos humanos; Pacto de San José; https://purl.org/pe-repo/ocde/ford#5.05.01